2019
DOI: 10.1292/jvms.18-0253
|View full text |Cite
|
Sign up to set email alerts
|

X monosomy in the endangered Kiso horse breed detected by a parentage test using sex chromosome linked genes and microsatellites

Abstract: A routine parentage test as part of a conservation program for Kiso horses identified a possible sex chromosome anomaly in a 7 months-old filly because of an aberrant result using LEX3, an X-linked marker. We then analyzed X-linked markers (LEX26, TKY38, and TKY270), Y-linked markers (Eca.YH12, Eca.YM2, Eca.YA16, and the sex-determining region Y gene), and an X/Y marker (Amelogenin gene). This analysis demonstrated that the filly had not inherited an X chromosome from her sire. A karyotyping analysis confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The International Society of Animal Genetics (ISAG) recommends the use of a properly standardized panel of 17 microsatellite markers for horses, located on 12 different autosomes and the X chromosome. By adding to this set additional X and Y chromosome markers, whole-genome STR genotyping for parentage testing can simultaneously be used for the initial detection of chromosomal aberrations, such as monosomy, trisomy, XY sex reversal syndrome and chimerism [ 53 , 126 , 127 , 194 , 195 , 196 ]. Microsatellite genotyping has also been used to determine the parental origin of an aberrant chromosome [ 27 , 197 ] and in a study of two cloned horses, one with a de novo autosomal translocation, to confirm that the clones and their sire were genetically identical [ 54 ].…”
Section: Molecular Cytogenetic Methods and Applicationsmentioning
confidence: 99%
“…The International Society of Animal Genetics (ISAG) recommends the use of a properly standardized panel of 17 microsatellite markers for horses, located on 12 different autosomes and the X chromosome. By adding to this set additional X and Y chromosome markers, whole-genome STR genotyping for parentage testing can simultaneously be used for the initial detection of chromosomal aberrations, such as monosomy, trisomy, XY sex reversal syndrome and chimerism [ 53 , 126 , 127 , 194 , 195 , 196 ]. Microsatellite genotyping has also been used to determine the parental origin of an aberrant chromosome [ 27 , 197 ] and in a study of two cloned horses, one with a de novo autosomal translocation, to confirm that the clones and their sire were genetically identical [ 54 ].…”
Section: Molecular Cytogenetic Methods and Applicationsmentioning
confidence: 99%
“…Mares with X monosomy are infertile and have irregular or absent oestrous cycles and small gonads lacking follicular development . Short stature is observed in some cases; however, individuals with normal appearance and normal external female genitalia are also reported . The frequency of X monosomy has been estimated at ~3%, based on cytogenetic screening of 262 young mares .…”
Section: Introductionmentioning
confidence: 99%
“…3 Short stature is observed in some cases; 4 however, individuals with normal appearance and normal external female genitalia are also reported. 5 The frequency of X monosomy has been estimated at ~3%, based on cytogenetic screening of 262 young mares. 6 Another analysis of microsatellite X-linked markers in a population of 17,471 newborn foals suggested that the incidence is much lower, at 0.15%.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen years later, Power [ 34 ] reported up to 400 individuals carrying CNAs, of which over 95% were related to fertility problems. Thirty years later, it became clear that ECAX monosomy, in its true (63,X; [ 35 ]) or 64,XX/63,X mosaic [ 36 ] forms, together with 64,XYdsd sex reversal mares [ 19 ], are the most common presentations in the species. Both cases are associated with a normal mare phenotype with a lack of development of the internal reproductive organs [ 37 ].…”
Section: Copy Number Abnormalities and Fertility: The Role Of The mentioning
confidence: 99%